Gelasimus splendidus Stimpson, 1858 (Crustacea: Brachyura: Ocypodidae), a valid species of fiddler crab from the northern South China Sea and Taiwan Strait - Shih, Hsi-Te; Ng, Peter K. L.; Wong, Kingsley J. H.; Chan, Benny K. K. (Zootaxa, 2012)
The fiddler crab, Uca splendida (Stimpson, 1858) has been synonymized under Uca crassipes (White, 1847) since Crane(1975). Studies of specimens from the Hong Kong type locality and adjacent areas of China, Taiwan and Vietnam showthat U. splendida is a valid species, with a characteristic suite of carapace and gonopod features as well as a distinctcytochrome oxidase I (COI) signature. Genetic work shows that U. splendida belongs to a well-supported clade and is thesister species of U. crassipes. The distribution of U. splendida is restricted to continental East and continental SoutheastAsia, in contrast to the oceanic distribution of U. crassipes. Both species, however, are sympatric in Penghu Islands, western Taiwan and Dongsha Island (=Pratas Island).